2020
DOI: 10.18203/issn.2454-5929.ijohns20201002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of the patients with oral squamous cell carcinoma: a tertiary institutional study

Abstract: <p class="abstract"><strong>Background:</strong> Oral cancer consists of a group of neoplasms affecting any region of the oral cavity. This term is commonly used interchangeably with oral squamous cell carcinoma (OSCC), representing the most frequent of all oral neoplasms. Factors affecting the development of the oral squamous cell carcinoma are tobacco use, alcohol consumption, low socio-economic status, poor hygiene, poor diet, viral infection like HPV, ill-fitting dentures, jagged teeth.&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…(5) In our study period from January 2017 to December 2020, we observed female predominance which is similar to studies conducted in India and Turkey (8) (12,13). Buccal mucosa (44%) was the most common site followed by lower gingivo-buccal sulcus (21%) in this study which is similar to a study conducted by Rahman et al, and also some Indian and Sri-Lankan Studies (6,1,10,14) This is due to the fact that most of the patients keep tobacco in the form of quid in the buccal sulcus. It is also a true fact for Bangladesh that tobacco and its related products are available at an affordable cost making it a habit for many rural people.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(5) In our study period from January 2017 to December 2020, we observed female predominance which is similar to studies conducted in India and Turkey (8) (12,13). Buccal mucosa (44%) was the most common site followed by lower gingivo-buccal sulcus (21%) in this study which is similar to a study conducted by Rahman et al, and also some Indian and Sri-Lankan Studies (6,1,10,14) This is due to the fact that most of the patients keep tobacco in the form of quid in the buccal sulcus. It is also a true fact for Bangladesh that tobacco and its related products are available at an affordable cost making it a habit for many rural people.…”
Section: Discussionsupporting
confidence: 89%
“…Malhotra et al, showed that mandibular alveolus was the most frequent site followed by Buccal mucosa (15). Andisheh-Tadbir et al, and most of the western literature stated that tongue was the most common site followed by buccal mucosa (1) (10).…”
Section: Discussionmentioning
confidence: 99%